A novel G-quadruplex motif in the Human MET promoter region. Issue 6 (29th November 2017) - Yan, Jing; Zhao, Deming; Dong, Liping; Pan, Shuang; Hao, Fengjin; Guan, Yifu
Abstract : It is known that the guanine-rich strands in proto-oncogene promoters can fold into G-quadruplex structures to regulate gene expression. An intramolecular parallel G-quadruplex has been identified in MET promoter. It acts as a repressor in regulating MET expression. However, the full guanine-rich region in MET promoter forms a hybrid parallel/antiparallel G-quadruplex structure under physiological conditions, which means there are some antiparallel and hybrid parallel/antiparallel G-quadruplex structures in this region. In the present study, our data indicate that g3-5 truncation adopts an intramolecular hybrid parallel/antiparallel G-quadruplex under physiological conditions in vitro . The g3-5 G-quadruplex structure significantly stops polymerization by Klenow fragment in K + buffer. Furthermore, the results of circular dichroism (CD) spectra and polymerase stop assay directly demonstrate that the G-quadruplex structure in g3-5 fragment can be stabilized by the G-quadruplex ligand TMPyP4 (5, 10, 15, 20-tetra-(N-methyl-4-pyridyl) porphine). But the dual luciferase assay indicates TMPyP4 has no effect on the formation of g3-5 G-quadruplex in HepG2 cells. The findings in the present study will enrich our understanding of the G-quadruplex formation in proto-oncogene promoters and the mechanisms of gene expression regulation.